2016
DOI: 10.1016/j.crci.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Biomass conversion to hydrogen-rich synthesis fuels using water steam plasma

Abstract: In this study, an experimental plasma-chemical reactor equipped with an arc discharge water steam plasma torch was used for biomass conversion to hydrogen-rich synthesis fuels. Glycerol and crushed wood were used as biomass sources. The effects of different conversion parameters including the water steam flow rate, treated material flow rate, and plasma torch power were studied. The experimentally obtained results were compared with the model based on the thermodynamic equilibrium. Additionally, the quantifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 29 publications
(33 reference statements)
1
9
0
2
Order By: Relevance
“…Meanwhile, C 2 H 4 and C 2 H 6 contents were small and thus had no apparent change. These results indicated that increasing the temperature is conducive to reforming reactions in equal (8). Notably, as the temperature increased, CH 4 content decreased from 11.24% to 3.83% and CO 2 content decreased from 20.04% to 2.40%, whereas CO content increased from 11.76% to 36.99%.…”
Section: Inuence Of Weight Hourly Space Velocity (Whsv) On Gas Distrmentioning
confidence: 83%
See 1 more Smart Citation
“…Meanwhile, C 2 H 4 and C 2 H 6 contents were small and thus had no apparent change. These results indicated that increasing the temperature is conducive to reforming reactions in equal (8). Notably, as the temperature increased, CH 4 content decreased from 11.24% to 3.83% and CO 2 content decreased from 20.04% to 2.40%, whereas CO content increased from 11.76% to 36.99%.…”
Section: Inuence Of Weight Hourly Space Velocity (Whsv) On Gas Distrmentioning
confidence: 83%
“…7 In the past few years, biomass had become an attractive renewable source that plays a major role in renewable energy production. 8 In China, the yield of rice husk reached 56 516.50 Â 10 4 t in 2016. As usually, a part of rice husk was used as the poultry fee.…”
Section: Introductionmentioning
confidence: 99%
“…The other type of experimental equipment for destruction of hazardous waste has been installed in Lithuanian Energy Institute (LEI) [11,14]. It consists of a plasma jet reactor with DC arc plasma source capacity of up to 90 kW.…”
Section: Plasma Processing Of Hazardous Wastementioning
confidence: 99%
“…In the last few decades, the problems of carbon-containing materials reforming into synthesis gaseous fuel-mixture CO and H 2 -by means of plasma technologies were widely discussed in the scientific literature [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. This syngas can be used for heat or electrical energy production [13].…”
Section: Introductionmentioning
confidence: 99%
“…LEI atlikti organinių medžiagų skaidymo bandymai [25,26]. Konversijai vykdyti pasirinktos angliavandenilius turinčios dujos ir įvestos į plazmocheminį reaktorių.…”
Section: Vandens Garo Plazminė Technologijaunclassified